Intelligent Smart Home Automation and Security System Using Arduino and Wi-fi (International Journal of Engineering and Computer Science, 2017)
This paper provides a low cost-effective and flexible home control and monitoring system with the aid of an integrated micro-web server with internet protocol (IP) connectivity for access and to control of equipment and devices remotely using Android-based smartphone app. The proposed system does not require a dedicated server PC with respect to similar systems and offers a new communication protocol for monitoring and controlling the home environment with more than just switching functionality. Smart home interfaces and device definitions to ensure interoperability between Wi-fi devices from various manufacturers of electrical equipment, meters and smart energy enables products to allow manufactured. In this project gives the intelligent operation for lamps and fans. Here the system is connected with temperature control and lamp control. Light dependent resistor (LDR) and Temperature sensor (LM35) are the main components for this automatic control of lamps and fans. Here the LDR is responsible for lamp control and LM35 is responsible for controlling the operation of fan. The proposed home energy control systems design intelligent services for users and provides, The proposed system are implemented with smartphone.